Don't Be Evil Should We Use Google in Schools? - Krutka, Daniel G (Conjugation of 5-azido-3-oxapentyl glycosides with thiolated proteins through the use of thiophilic derivatives, 2021)
© Association for Educational Communications & Technology 2021, corrected publication 2021.